PRACTICAL APPLICATION OF THE THEORY OF PRIVATE MONEY IN THE CRYPTOCURRENCY MARKET - Ilya A, Evdokimov; Nikita I, Frolov; Denis M, Lysanov; Anton N, Karamyshev; Aleksey G, Isavnin (Gênero & Direito, 2019)
The article considers the main aspects of the theory of F.A. von Hayek. The effectiveness of competition has been proved as a way to select the best currencies, which are characterized by high liquidity, transparent emission, and active work in the information space. And also in this article, the power of the influence of the press factor on the theory of Private Money by F. A. von Hayek is considered. The effectiveness of this factor, which acts as a filter of a low-quality product, allowing market participants to filter out unreliable currencies, has been proved.